Predictors of academic performance: National Senior Certificate versus National Benchmark Test - Rankin, Neil; Schöer, Volker; Claire Sebastiao, Claire Sebastiao; van Walbeek, Corné (South African Journal of Higher Education, 2016)
This paper considers students’ performance in an identical Economics test at two universities to investigate the predictive power of the NBT against that of Mathematics in the National Senior Certificate (NSC) exam. We find that, on average, both NBT and NSC results are useful predictors of performance in Economics. However, for students whose NSC Mathematics marks are close to the minimum admission requirements, the NBT scores (especially in Quantitative and Academic Literacy) are better measures of academic potential. Thus, an admission criterion based on NSC marks alone may exclude students with the academic potential to pass university courses, while it may admit students that are not sufficiently prepared for university studies. Our findings suggest that the NBT should not be used as an alternative to the NSC, but as a complement for admission and correct placement of lower performing applicants.